Konsistensi Tata Tulis Karya Ilmiah Skripsi pada Program Studi PBSI FKIP Univet Bantara Sukoharjo - Sri Wahono Saptomo, Sukarno, Suparmin, (Universitas Veteran Bangun Nusantara, 2022)
The objective of this research is to describe the consistency of (1) the table presentation in the paper at Indonesian Departement Program, FKIP Universitas Veteran Bangun Nusantara Sukoharjo tahun 2021, (2) the diagram presentation in that paper, (3) the bibliography writing, and (4) the theoretical construction about the problem of the paper that is represented in that tittle of this paper. This research approach is the qualitative research approach. Research subject of this research is the paper that is called “skripsi” at Indonesian Departement Program, FKIP Universitas Veteran Bangun Nusantara Sukoharjo. There are ten (10) tittles for this data that isi conducted by purposive random sampling. The collecting data is conducted by reading and writing to these documents. The collecting data is analyzed by qualitative. The result of this research can be cobcluded as follow (1) there are some inconsistency about the table presentation at these papers, as numbering, variation, letters, positioning the tittle and table, presenting table, spacing of text and table, (2) the drawing still shows the inconsistency to spacing and functuation application, the infmation unit bounded, using letters, and (4) constructiong of the theory for the scientific problem that is represented shows the patterns that irrelevant by the main content of the construction theory, the academic tittle, and paper focus.